2017
DOI: 10.3389/fmed.2017.00185
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Mitochondrial-Encoded Genes in Blood Differentiate Acute Renal Allograft Rejection

Abstract: Despite potent immunosuppression, clinical and biopsy confirmed acute renal allograft rejection (AR) still occurs in 10–15% of recipients, ~30% of patients demonstrate subclinical rejection on biopsy, and ~50% of them can show molecular inflammation, all which increase the risk of chronic dysfunction and worsened allograft outcomes. Mitochondria represent intracellular endogenous triggers of inflammation, which can regulate immune cell differentiation, and expansion and cause antigen-independent graft injury, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…When the kidney is damaged, plasma dmtDNA levels increase, which may be accompanied by more antigen exposure, resulting in increased AR incidence. In contrast, increased dmtDNA levels may not only trigger inflammation, but may also lead to AR [ 28 , 29 ]. Elevated dmtDNA levels are an independent risk factor not only for DGF, but also for AR.…”
Section: Discussionmentioning
confidence: 99%
“…When the kidney is damaged, plasma dmtDNA levels increase, which may be accompanied by more antigen exposure, resulting in increased AR incidence. In contrast, increased dmtDNA levels may not only trigger inflammation, but may also lead to AR [ 28 , 29 ]. Elevated dmtDNA levels are an independent risk factor not only for DGF, but also for AR.…”
Section: Discussionmentioning
confidence: 99%
“…Nonsteroidal anti‐inflammatory drugs (NSAIDs) are widely used to alleviate inflammation (Moore et al., 2019 ). Even prolonged use of NSAIDs can result in gastric and renal toxicity (Magni et al., 2021 ), mainly due to the nonselective inhibition of COX‐1 and COX‐2 (Roedder et al., 2017 ). It is believed that currently used anti‐inflammatory drugs, including opiates and non‐NSAIDs, have associated toxic effects like gastric and renal ulcers and low potentiality (Coban & Degim, 2020 ; Phueanpinit et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown an important link between mitochondrial dysregulation and allograft rejection 19–26 . Mitochondrial fusion/fission plays an important role in regulating mitochondrial fitness and cellular health.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown an important link between mitochondrial dysregulation and allograft rejection. [19][20][21][22][23][24][25][26] Mitochondrial fusion/fission plays an important role in regulating mitochondrial fitness and cellular health. Fusion is mediated by several key machinery proteins, including mitofusin-1, mitofusin-2, and optic atrophy-1.…”
Section: Introductionmentioning
confidence: 99%